The Arctic Voice at the UN Climate Negotiations: Interplay Between Arctic & Climate Governance - Duyck, Sébastien, 1983- (2015)
During the past decade, the Arctic has progressively gained the status of a “global barometer” of the implications of climate change. As governments finalize in 2015 the negotiations towards a new climate change agreement and as the priorities of the Arctic Council are shifting towards a stronger focus on climate change, the current year offers a timely opportunity to review the interplay between Arctic policies and the international climate change regime. Indeed, several of the Arctic states have committed through their Arctic strategies to highlight regional concerns and circumstances in relevant international forums. Additionally, the states and organizations with observer status at the Arctic Council are expected to bring Arctic concerns to global decision-making bodies. The Arctic Council itself has referred repeatedly to the UN Framework Convention on Climate Change in many of its ministerial declaration. Consequently, this thesis aims at assessing whether the “Arctic voice” has been effectively carried in the climate change process and to what extent the outcomes of this process address, or are informed by, issues specific to the Arctic. The thesis begins with a review of the consideration of climate impacts and circumstances specific to the Arctic through regional and international cooperation. It then assesses how different actors have raised Arctic concerns in the international climate negotiations. While these negotiations are not designed in a manner facilitating the consideration of regional specificities, governments have several opportunities to raise particular concerns through the process, either as they report on their national circumstances or when they express views related to the development of the climate regime. Non-state actors – including regional forums, NGOs and indigenous peoples, can also contribute to the process, particularly in relation to the construction of public discourses around the negotiations. The present research thus reviews systematically the contributions made by ...